Right Fusiform Gyrus Stroke Presenting With Acute Prosopagnosia - Mahmoud Fayed; Fahad Khan; Frederick Abraham; Gabriel Bonnell; Teng J. Peng (Annals of Internal Medicine: Clinical Cases)
An 82-year-old right-handed man with hypertension and hyperlipidemia presents to the hospital with symptoms of altered vision and difficulty recognizing people despite having normal visual acuity. He was diagnosed with prosopagnosia, and neuroimaging demonstrated an acute infarction in the right fusiform gyrus. Acquired prosopagnosia is a rare neurologic syndrome characterized by the sudden inability to recognize familiar or new faces. Sudden onset of prosopagnosia is a cortical sign that may be a manifestation of acute ischemic stroke.